Coordination of the Revolutionary Courts in the Islamic Republic of Iran until 1981 AD (Journal of the College of Basic Education, 2024)
The Revolutionary Courts continued to play an important role in consolidating and preserving the foundations of the Iranian regime by pursuing a policy of political and ideological exclusion, trial, repression, and elimination of all those who oppose the regime intellectually, politically, and ideologically, in order to preserve the revolution and its gains. These courts have claimed the lives of tens of thousands of opponents and political opponents on charges of War, domestic corruption, and the threat to national security. Given the challenges and risks that the Iranian regime has recently begun to face, it seems that these courts will continue to function, and they will continue to do so as long as the regime exists, and that regime officials will not respond to criticism. And international calls to dismantle it... pressure, as these regimes have proven to be suitable tools to effectively silence dissenting voices. Either through imprisonment or threats, or fleeing out of Iran for fear of prosecution. Abolishing these courts or limiting their role in the near future remains unlikely, especially in light of popular discontent and protests in cities across Iran. Many times, this went beyond the need to improve the economy and living conditions to the rejection of the entire system and the condemnation of its leaders.